High Performance Dye-Sensitized Solar Cells with Record Open Circuit Voltage using Tin Oxide Nanoflowers Developed by Electrospinning - M. M., Yusoff; Rajan, Jose; Kumar, E. Naveen; Archana, P. S.; Vijila, C.; Ramakrishna, Seeram (Royal Society of Chemistry, 2012)
Flower shaped nanostructures of an architypical transparent conducting oxide, SnO2, have been synthesized by an electrospinning technique for the first time by precisely controlling the precursor concentration in a polymeric solution. The flowers were made up of nanofibrils of diameter [similar]70–100 nm, which in turn consisted of linear arrays of single crystalline nanoparticles of size 20–30 nm. Mott–Schottkey analysis shows that flowers have an order of magnitude higher electron density compared with the fibers despite their chemical similarity. Dye-sensitized solar cells fabricated using the flowers showed a record open circuit voltage of [similar]700 mV and have one of the highest photoconversion efficiencies so far achieved with SnO2 and the iodide/triiodide electrolyte. The photoaction spectra and impedance spectroscopic measurements show that the flowers are characterized by a higher electron lifetime, owing to their enhanced crystallinity, compared to the conventional fibrous structure.